Niflumic Acid Reverses Airway Mucus Excess and Improves Survival in the Rat Model of Steroid-Induced Pneumocystis Pneumonia - Pérez, Francisco J.; Iturra, Pablo A.; Ponce, Carolina A.; Magne, Fabien; Garcia-Angulo, Víctor; Vargas, Sergio L. (Frontiers in Microbiology, 2019)
The concerted action of innate and adaptive immune responses is essential to fight infections and although the role of adaptive immunity in fighting Pneumocystis infection is well accepted, the role of innate responses remains largely unexplored. Mucus is an essential component of innate immune responses, and Pneumocystis-associated goblet-cell-derived CLCA1 protein hyperexpression plus mucus excess have been documented in infant autopsy lungs and in murine models of primary infection alerting of innate immune system immunopathology associated to Pneumocystis infection. Nonetheless, whether blocking mucus innate immune pathways can decrease Pneumocystis-related immunopathology is unknown. Furthermore, current treatment of Pneumocystis pneumonia (PcP) relies on anti-Pneumocystis drugs plus steroids the most potent anti-inflammatory drugs available that ablate cellular immune responses. In the current study, we used the steroid-induced rat model of Pneumocystis pneumonia (PcP) to evaluate inflammation and mucus progression, and to further test the effect of niflumic acid (NFA), a potent CLCA1 blocker fenamate-type drug, in decreasing Pneumocystis-associated immunopathology. In this model, animals acquire Pneumocystis spontaneously and pneumonia develops owing to the immunodeficiency resulting from apoptosis of immune cells induced by steroids. Steroid administration led to decreased animal weight evidencing severe immunosuppression and to significant Pneumocystis-associated pulmonary edema as evidenced by wet-to-dry lung ratios that doubled those of uninfected animals. Inflammatory cuffing infiltrates were noticed first around lung blood vessels and following in bronchi and both increased progressively. Similarly, airway epithelial and lumen mucus increased progressively in parallel to increasing levels of MUC5AC and CLCA3, the murine homolog of hCLCA1, and document developing CLCA1-associated immunopathology during steroid induced PcP. Notably, administration of NFA caused a significant decrease in Pneumocystis-associated inflammation, total mucus, MUC5AC and CLCA3. Most relevant, NFA treatment associated with increased survival at 8-weeks of steroids. This warrants evaluation of CLCA1 blockers as adjunctive therapy in PcP and describes a simple model to evaluate therapeutic interventions for steroid resistant mucus, a common condition in patients with chronic lung disease like asthma, chronic obstructive pulmonary disease (COPD) and cystic fibrosis.